(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The current study set out to look at two species of ducks belonging to the Phalacrocorcidae family that are found in the Eastern Hammar Marsh in the Al-Mashab district of Basrah Province, in southern Iraq. We checked these birds for parasitic worms. The study sample included 18 cormorants (Phalacrocorax carbo), where three cestoda species were discovered: Glossocercus auritus, Paradilepis scolecina, and Bancroftiella sp. In addition, 84 pygmy cormorants (Phalacrocorax pygmeus) were also included in the study. These included four cestoda species: Glossocercus auri In Iraq, records of the two species Glossocercus auritus and Bancroftiella ardeae were made for the first time.